The moth catcher [compact disc, unabridged] - Cleeves, Ann (Cleeves, Ann. Vera Stanhope series., 2016)
When a housesitter is found dead at a Valley Farm country home, Vera Stanhope, accompanied by detectives Holly and Joe, discovers a second body in the house's attic before realizing that the community keeps bizarre secrets.